2004
DOI: 10.1007/s00127-004-0834-5
|View full text |Cite
|
Sign up to set email alerts
|

Personality, perceived parental rejection and problem behavior in adolescence

Abstract: Several clear moderating effects of the personality type x gender groups were found on associations between perceived parental rejection, depression and aggression. Future research should focus on these specific combinations instead of using either personality types or gender separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 43 publications
8
67
1
13
Order By: Relevance
“…It is known that undercontrollers are very impulsive and often have academic and behavioural problems, which could be a possible cause for serious conflicts with other people. The negative feelings that are related to these conflicts might cause a negative mood (Akse et al, 2004;Dubas et al, 2002), which could lead them to exhibit more overcontrolling characteristics and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that undercontrollers are very impulsive and often have academic and behavioural problems, which could be a possible cause for serious conflicts with other people. The negative feelings that are related to these conflicts might cause a negative mood (Akse et al, 2004;Dubas et al, 2002), which could lead them to exhibit more overcontrolling characteristics and…”
Section: Discussionmentioning
confidence: 99%
“…We used the k-means clustering procedure to construct the personality types on the basis of the Big Five dimensions (Akse et al, 2004;Dubas et al, 2002) one of the three clusters on the basis of the correspondence between the cluster centre and the individual's mean. The means within a cluster must correspond highly with each other, whereas the means between the clusters must differ highly from each other.…”
Section: Personalitymentioning
confidence: 99%
“…Some recent personcentered studies also reported findings in line with this model, as adolescents who were lower on Extraversion were more at risk for developing a depressive mood (Akse, Hale, Engels, Raaijmakers, & Meeus, 2004, 2007aDubas, Gerris, Janssens, & Vermulst, 2002;Van Aken, Van Lieshout, Scholte, & Haselager, 2002). In addition, adolescents who changed from an introverted and socially withdrawn personality type to a personality type that was more extraverted and less socially withdrawn, displayed decreasing levels of internalizing problem behavior, while increasing levels of internalizing problem behavior accompanied personality type changes in the opposite direction (Akse, Hale, Engels, Raaijmakers, & Meeus, 2007b).…”
Section: Introductionmentioning
confidence: 62%
“…Undercontrollers have excessively low levels of ego-control, resulting in an inability to delay gratification, and a tendency to respond immediately and impulsively to environmental triggers (Block & Block, 1980). Because Robins et al (1996) demonstrated that Resilients, Undercontrollers, and Overcontrollers have clearly distinguishable Big Five profiles, several subsequent studies (e.g., Akse, Hale, Engels, Raaijmakers, & Meeus, 2004;Asendorpf, Borkenau, Ostendorpf, & Van Aken, 2001;Dubas, Gerris, Janssens, & Vermulst, 2002) extracted personality types directly from Big Five data. For this purpose, they applied cluster analysis to Big Five ratings (see for example Akse, Hale, Engels, Raaijmakers, & Meeus, 2007, for an explanation of this technique).…”
Section: Variable-centered Approaches To Personalitymentioning
confidence: 99%
See 1 more Smart Citation